Underwater wireless sensor networks transmission and characteristics protocols A survey - Zainab saad karam; Rawaa Hamaz Ali; baqer obaiad Al-nashy (Genius Journals, 2023)
Due to the increased use of marine resources and the fast development of research on wireless sensor networks on land, UWSNs (underwater wireless sensor networks) have evolved into a new research hotspot. The routing protocol is one of the most important parts of UWSNs. This paper shows several traditional routing algorithms for location, sector, reinforcement learning, and intelligent optimization. The paper ends with a summary and a look at where research on underwater wireless sensor network routing algorithms is likely to go in the future.
Keywords: Underwater; wireless sensor network; Routing protocols